Simultaneous electrical recording of cardiac electrophysiology and contraction on chip. Issue 10 (27th April 2017) - Qian, Fang; Huang, Chao; Lin, Yi-Dong; Ivanovskaya, Anna N.; O'Hara, Thomas J.; Booth, Ross H.; Creek, Cameron J.; Enright, Heather A.; Soscia, David A.; Belle, Anna M.; Liao, Ronglih; Lightstone, Felice C.; et al.
Abstract : We report a new heart-on-chip design capable of electrical stimulation, recording of growth, contraction and activating map from in vitro -cultured human cardiac tissues. Abstract : Prevailing commercialized cardiac platforms for in vitro drug development utilize planar microelectrode arrays to map action potentials, or impedance sensing to record contraction in real time, but cannot record both functions on the same chip with high spatial resolution. Here we report a novel cardiac platform that can record cardiac tissue adhesion, electrophysiology, and contractility on the same chip. The platform integrates two independent yet interpenetrating sensor arrays: a microelectrode array for field potential readouts and an interdigitated electrode array for impedance readouts. Together, these arrays provide real-time, non-invasive data acquisition of both cardiac electrophysiology and contractility under physiological conditions and under drug stimuli. Human induced pluripotent stem cell-derived cardiomyocytes were cultured as a model system, and used to validate the platform with an excitation–contraction decoupling chemical. Preliminary data using the platform to investigate the effect of the drug norepinephrine are combined with computational efforts. This platform provides a quantitative and predictive assay system that can potentially be used for comprehensive assessment of cardiac toxicity earlier in the drug discovery process.